2012
DOI: 10.1111/j.1748-1716.2011.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

CB1 receptor antagonists: new discoveries leading to new perspectives

Abstract: CB(1) receptor antagonists were among the most promising drug targets in the last decade. They have been explored and found to be effective as therapeutic agents for obesity and related cardiometabolic problems; however, use of rimonabant, the first marketed CB(1) receptor antagonist, has been suspended because of its anxiogenic and depressogenic side effects. Because some other antiobesity drugs, like dexfenfluramine or sibutramine, were also suspended, the unmet need for drugs that reduce body weight becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 157 publications
(365 reference statements)
1
54
0
Order By: Relevance
“…The idea of treating tobacco dependence and obesity together is a provocative one. Rimonabant, a cannabinoid receptor antagonist, has been used to treat obesity 96 and nicotine dependence 97 , and is also effective against the metabolic syndrome 98 . However, rimonabant had adverse psychiatric effects and did not receive FDA approval 96 .…”
Section: Smoking Cessationmentioning
confidence: 99%
“…The idea of treating tobacco dependence and obesity together is a provocative one. Rimonabant, a cannabinoid receptor antagonist, has been used to treat obesity 96 and nicotine dependence 97 , and is also effective against the metabolic syndrome 98 . However, rimonabant had adverse psychiatric effects and did not receive FDA approval 96 .…”
Section: Smoking Cessationmentioning
confidence: 99%
“…The reaction was cooled down to r.t., poured into water, extracted with DCM, dried over MgSO 4 , filtered and the solvent was evaporated under reduced pressure. The crude product was purified by flash chromatography (Hexane/EtOAc 6:4) to give the desired compound 1a-c. 2,123.1,125.8,127.9,128.0,128.3,129.0,129.2,129.7,130.2,130.4,131.1,133.6,134.0,135.9,136.5,136.8,137.3,142.5,143.9,146.2;MS (ESI) 8,83.2 (d,115.5,120.7,123.6,124.2,125.0,127.9 (2C),129.0,130.2,131.1,134.0,136.0,136.3,136.5,137.1,139.3,142.4,143.9,146. = 5.7 Hz),1H),6.73 (d,1H,J = 3.8 Hz),6.82 (d,1H,J = 3.8 Hz),7.34 (dd,1H,J = 2.2,8.5 Hz),7.40 (d,1H,J = 8.5 Hz),7.50 (d,…”
Section: Suzuki-miyaura Cross Coupling: General Proceduresmentioning
confidence: 99%
“…CB 1 receptors are localised predominantly in the brain [2] whereas CB 2 receptors are more abundant in peripheral nervous system (PNS) cells [3], although some studies have shown the presence of CB 1 in the PNS [4] and of CB 2 in the central nervous system, albeit in low density [5]. CB 1 receptors have been associated with a number of disorders, including depression [6], anxiety [7], stress [8], schizophrenia [9], chronic pain [10] and obesity [11]. For this reason, several cannabinoid ligands were developed as drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Ability of neutral antagonists 'not to affect whole gut transit' may be a key for the future development of CB1 receptor antagonists [10]. Kirilly et al [30] have reviewed the adverse effects associated with the peripheral acting CB1 receptor antagonists like gastrointestinal disorders such as nausea, vomiting, diarrhea and dyspepsia, and nervous system disorders such as dizziness, vertigo and hypesthesia and other events like fatigue, hot flush, tendonitis and contusion. There are evidences indicating the existence of allosteric binding sites on CB1 receptors [31].…”
Section: Introductionmentioning
confidence: 99%